1999
DOI: 10.1093/glycob/9.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the trypanosomal and human GlcNAc-PI de-N-acetylases of glycosylphosphatidylinositol membrane anchor biosynthesis

Abstract: De-N-acetylation of N-acetylglucosaminyl-phosphatidylino-sitol (GlcNAc-PI) is the second step of glycosylphosphatidylino-sitol (GPI) membrane anchor biosynthesis in eukaryotes. This step is a prerequisite for the subsequent processing of glucosaminyl-phosphatidylinositol (GlcN-PI) that leads to mature GPI membrane anchor precursors, which are transferred to certain proteins in the endoplasmic reticulum. In this article, we used a direct de-N-acetylase assay, based on the release of [14C]acetate from synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…The TbGPI12 gene has been shown here to be a single-copy gene that is essential for the disease-causing bloodstream form of T. brucei, thus validating this particular enzyme as a potential drug target for the development of therapeutic agents against African sleeping sickness and, possibly, against related parasitic diseases, such as the leishmaniases and Chagas' disease. The genetic validation of GlcNAc-PI de-N-acetylase as an antitrypanosomal target is particularly significant because there has been considerable biochemical characterization of this enzyme (32)(33)(34)(35)(36)(37)(38). Attractive features of this potential drug FIG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TbGPI12 gene has been shown here to be a single-copy gene that is essential for the disease-causing bloodstream form of T. brucei, thus validating this particular enzyme as a potential drug target for the development of therapeutic agents against African sleeping sickness and, possibly, against related parasitic diseases, such as the leishmaniases and Chagas' disease. The genetic validation of GlcNAc-PI de-N-acetylase as an antitrypanosomal target is particularly significant because there has been considerable biochemical characterization of this enzyme (32)(33)(34)(35)(36)(37)(38). Attractive features of this potential drug FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline was added back to one of the cultures after 6 days (C, arrow), leading to rapid recovery of the culture. target include: (i) relatively low identity and similarity (36 and 54%) between the T. brucei and human enzyme peptide sequences; (ii) significant differences between the substrate specificities of the T. brucei and human enzymes (37,38); and (iii) the recent synthesis of two potent (IC 50 , 8 nM) parasite-specific suicide substrate inhibitors of the enzyme (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, GPI biosynthetic pathways are suitable targets for drug development. It was shown that a block in GPI synthesis by disruption of the PIG-B gene makes blood stages of T. brucei nonviable (48), and specific inactivators have been proposed as possible targets for chemotherapy against sleeping sickness (59,61). While GPI synthesis is also important in mammals, especially for embryogenesis (71), mammalian cells in culture have been shown to survive well in culture without it (46).…”
mentioning
confidence: 99%
“…The first steps in the biosynthesis of GPIs lead to the formation of a glucosaminylinositol-phosphate-lipid intermediate by the transfer of Nacetylglucosamine (GlcNAc) from UDP-GlcNAc to an inositol phosphate lipid and the immediate de-N-acetylation of the GlcNAc. By using different chemically synthesized GlcNAcPtdIns analogues in a de-N-acetylase assay, differences in substrate specificities have been established between the trypanosomal enzyme and a mammalian enzyme [9]. In mammalian cells and yeast, intermediates of GPI biosynthesis receive a palmitoyl residue on the inositol ring before the attachment of the first mannose residue of the evolutionarily conserved trimannosyl core glycan, whereas in trypanosomes the first mannosylation step must precede palmitoylation of the inositol ring [10,11].…”
Section: Introductionmentioning
confidence: 99%